Freedom as Social Practice: Reconstructing Religious Freedom in Everyday Life - Michele Garau; Giacomo Bazzani (Religions, 2025)
This article examines how religious freedom is enacted and redefined through everyday practices in pluralistic urban settings. Moving beyond the classical notion of negative liberty as non-interference, it explores the social conditions that enable or constrain the practical expression of religious life. Drawing on forty-three qualitative interviews with religious leaders and civic actors in Florence, Italy, the study analyses how religious freedom is experienced across institutional contexts such as hospitals, schools, prisons, workplaces, and sport facilities. The findings reveal a persistent tension between formal legal rights and their uneven implementation in daily life. While legal guarantees are generally upheld, structural barriers and discretionary practices often hinder access to religious expression. At the same time, informal interactions, local networks, and dialogical engagement play a key role in supporting the concrete exercise of religious freedom. The article argues that freedom is not simply a legal status but a social process, realized through relational and institutional arrangements. By foregrounding the role of everyday interaction in shaping the conditions of freedom, this study contributes to broader sociological debates on pluralism, normativity, and the social foundations of institutional life.